Bioinformatics analysis of mRNA profiles and identification of microRNA-mRNA network in CD4+ T cells in seasonal allergic rhinitis. Issue 8 (August 2022) - Jin, Peng; Zhang, Hongping; Zhu, Xilin; Sun, Kaiyue; Jiang, Tao; Shi, Li; Zhi, Lili; Zhang, Hailing
Objective: We aimed to discover potential circulating genes and non-coding molecules (micro RNA [miRNA] and circular RNA [circRNA]) in CD4 + T cells in relation to seasonal allergic rhinitis (SAR). Methods: Microarray data of GSE50223 were obtained from the Gene Expression Omnibus database. Differentially expressed genes (DEGs) during and outside the pollen season were analyzed using R software and by Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes pathway analyses. The protein–protein interactions, modules, miRNAs targeting DEGs, merged miRNA–DEG networks, and circRNAs targeted with miRNAs were further analyzed. Results: We identified 211 DEGs during the pollen season and eight DEGs outside the season, of which only MMP12, NR4A2, and CD69 were differentially expressed both during and outside the pollen season. DEGs during the pollen season were enriched in the GO categories 'neutrophil degranulation', 'neutrophil activation involved in immune response', 'neutrophil mediated immunity', and 'neutrophil activation'. A significant module was identified with key nodes of CDK6 and hsa-miR-29b-3p. Six significant circRNAs were also identified. Conclusions: Some genes, miRNAs, and circRNAs in CD4 + T may play vital roles in SAR and may thus be potential targets for the prevention and treatment of SAR.